Nilai-nilai Pendidikan Karakter; Penguatan Berbasis Kegiatan Ekstrakurikuler Pramuka di Pesantren - Fathor Rozi; Uswatun Hasanah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
This study aims to understand how to carry out moral education through extracurricular activities in Islamic boarding schools. The values contained in scouts are very high, helping to install character values that are very suitable for basic students informing moral values and fostering personality values in them. The methodology or approach used in this paper is through a library research method or approach. Collect data at the same time By viewing and/or exploring several quality books, journals, and documents in print or electronic form and several sources of data or other information that are very important. Relaxation and research. Carrying out of extracurricular activities to increase the value of certain aspects What is found in the activities carried out including Take care of some things you can do Actually based on what students learn, or the environment needs. The process of cultivating personality values can be adjusted to the needs of students? The goal is that the values that can be instilled in students are correct internalization, especially in the selection or use of the scouting method.